1939
DOI: 10.1139/cjr39d-014
|View full text |Cite
|
Sign up to set email alerts
|

The Secretion of Crystalloids and Protein Material by the Pancreas in Response to Secretin Administration

Abstract: The concentrations of sodium, potassium, calcium, chloride, bicarbonate, and protein and non-protein nitrogen were determined in series of samples of pancreatic juice secreted by dogs in response to (a) constant rate of administration of secretin, (b) varied rate of administration of secretin, and (c) interrupted administration of secretin (rest period, 2 hr.). Spectroscopic as well as chemical methods were used in the analysis of the samples.The data indicate that the membranes of the pancreatic gland offer l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0
1

Year Published

1954
1954
1972
1972

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 7 publications
2
4
0
1
Order By: Relevance
“…Komarov, Langstroth, and McRae (1939) demonstrated that the fall in bicarbonate concentration was not influenced by simultaneous intravenous replacement of bicarbonate ions and this result has been confirmed in the present study. Komarov, Langstroth, and McRae (1939) and later Christodoulopoulos, Jacobs, and Klotz (1961) showed that if a pancreas was stimulated by a constant-dose infusion of secretin the flow ½/2 1 1½V2 2 2½V2 3 rate of pancreatic juice remained constant for several hours but that after a brief initial plateau S the bicarbonate concentration and output began to fall. Baron, Perrier, Janowitz, and Dreiling (1963) noted that continuous infusion of secretin change in secretin level in the body led to a fall in bicarbonate concentration intant dose infusion.…”
Section: Bicarbonate Outputsupporting
confidence: 90%
See 1 more Smart Citation
“…Komarov, Langstroth, and McRae (1939) demonstrated that the fall in bicarbonate concentration was not influenced by simultaneous intravenous replacement of bicarbonate ions and this result has been confirmed in the present study. Komarov, Langstroth, and McRae (1939) and later Christodoulopoulos, Jacobs, and Klotz (1961) showed that if a pancreas was stimulated by a constant-dose infusion of secretin the flow ½/2 1 1½V2 2 2½V2 3 rate of pancreatic juice remained constant for several hours but that after a brief initial plateau S the bicarbonate concentration and output began to fall. Baron, Perrier, Janowitz, and Dreiling (1963) noted that continuous infusion of secretin change in secretin level in the body led to a fall in bicarbonate concentration intant dose infusion.…”
Section: Bicarbonate Outputsupporting
confidence: 90%
“…Rawls, Wistrand, and Maren (1963) found that a metabolic acidosis produced by infusing hydrochloric acid intravenously reduced pancreatic flow and bicarbonate output very considerably. However, Komarov et al (1939) found that replacing the secreted bicarbonate by a separate intravenous infusion did not prevent the fall in bicarbonate concentration of the pancreatic juice and the same result has been demonstrated in this study.…”
Section: Bicarbonate Outputsupporting
confidence: 89%
“…Values for the concentration of calcium in the pure pancreatic juice of dogs have been given by Ball (1930), Johnston and Ball (1930), Komarov, Langstroth, and McRae (1939), Solomon (1952), McPherson, and Pace (1961, Herskovic, Wakim, Bartholomew, Cain, and Jones (1965), Zimmerman, Dreiling, Rosenberg, and Janowitz (1967). Most observations were made on the basal secretion, or after stimulation with secretin itself or of the secretin mechanism by instillation of hydrochloric acid into the duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…4 When stimulation is prolonged, bicarbonate concentration tends to fall and chloride concentration to rise despite constant rates ofsecretion ofjuice. This phenomenon has been observed in the isolated pancreas (Rothman and Brooks, 1965a), in canine pancreatic juice during secretin stimulation (Komarov, Langstroth, and McRae, 1939;Christodoulopoulos, Jacobs, and Klotz, 1961), and in man (Banwell, Northam, and Cooke, 1967). 5 Bicarbonate concentration falls as the volume of pancreatic juice (Baron, Perrier, Janowitz, and Dreiling, 1963) and of duodenal aspirate (Wormsley, 1968;Ribet et al, 1967) increases, as the magnitude of the secretin stimulus is raised.…”
mentioning
confidence: 90%